PENGARUH KUALITAS LAYANAN, KERAGAMAN PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Pada Annash Selluler Kendal) - Sandi Putra Pratama, 14.05.51.0202; Maskur, Ali (Students' Journal of Economic and Management, 2018)
The purpose of this study is to determine the effect of service quality, product diversity, and price perception on customer satisfaction and its impact on customer loyalty in Annash Selluler Kendal. The population in this study were customers in Annash Selluler Kendal. Sampling technique using purposive sampling. The sample criteria in this study are customers who have made purchases more than 3 times in Annash Selluler Kendal. Analyzer used is multiple linear regression. The result of this research can be concluded that: Service Quality have positive and significant effect to customer satisfaction. The diversity of products has a positive and significant impact on customer satisfaction. Price perceptions have a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant impact on customer loyalty. Keywords: Customer Quality, Product Diversity, Price Perception, Customer Satisfaction, Customer Loyalty